2017
DOI: 10.1016/j.pbb.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in chronic stress effects on cognition in rodents

Abstract: Chronic stress causes deleterious changes in physiological function in systems ranging from neural cells in culture to laboratory rodents, sub-human primates and humans. It is notable, however, that the vast majority of research in this area has been conducted in males. In this review, we provide information about chronic stress effects on cognition in female rodents and contrast it with responses in male rodents. In general, females show cognitive resilience to chronic stressors which impair male cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 53 publications
6
84
1
2
Order By: Relevance
“…The most typical measure for this task is the total number of arm entries to collect all the available food. Males have repeatedly been shown to use a lower number of total arm entries to complete this task [85][86][87][88][89], but there have also been a number of papers showing no sex difference in this measure [90,91]. This result has often been interpreted to mean that males are better at maintaining in mind which arms have already been visited, and thus that males have an advantage in working memory in general.…”
Section: Animal Assessments Of Working Memorymentioning
confidence: 99%
“…The most typical measure for this task is the total number of arm entries to collect all the available food. Males have repeatedly been shown to use a lower number of total arm entries to complete this task [85][86][87][88][89], but there have also been a number of papers showing no sex difference in this measure [90,91]. This result has often been interpreted to mean that males are better at maintaining in mind which arms have already been visited, and thus that males have an advantage in working memory in general.…”
Section: Animal Assessments Of Working Memorymentioning
confidence: 99%
“…Multiple previous studies show an association between levels of adult neurogenesis and performance in tasks measuring pattern separation, spatial discrimination, or cognitive flexibility (Clelland et al 2009; Cushman et al 2012; Hollands et al 2017; Pan et al 2012; Sahay et al 2011). Previous studies in rats and voles have shown the hippocampus to be a sexually dimorphic structure (Galea 2008; Luine et al 2017). For instance, estrogen increases neurogenesis during proestrus in female rats (Tanapat et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, similar to previous studies of Sprague Dawley and Fischer 344 rats (Spivey et al, ; Tropp & Markus, ), the present study found that female Long–Evans rats exhibited increased levels of locomotor activity in the open‐field test relative to the levels of male rats. Female rats have generally been observed to be more active than male rats (Luine, Gomez, Beck, & Bowman, ), possibly because male rats are more anxious and explore their environment more thoroughly, seeking places of refuge, than females or because they use different strategies than females do to explore novel environments (Alstott & Timberlake, ; Luine et al, ; Tropp & Markus, ).…”
Section: Discussionmentioning
confidence: 99%